BUYING YOUR WAY INTO HIGHER EDUCATION? LEARNING ENGLISH IN THE SHADOWS AND ITS IMPACT ON ADMITTING TO A HIGHLY SELECTIVE EMI UNIVERSITY IN KAZAKHSTAN - Yergazina, Azhar (Nazarbayev University Graduate School of Education, 2025)
English private tutoring (EPT) has expanded rapidly in Kazakhstan, especially among students preparing for high-stakes university entrance exams. Despite this growth, empirical research on EPT in Central Asia remains scarce. This qualitative study addresses this gap by investigating the EPT experiences of first-year undergraduate students in Kazakhstan, drawing on Benson’s (2011) four-dimensional model of out-of-class language learning: location, formality, locus of control, and pedagogy. Two research questions guided the study: (1) How are the four dimensions of location, formality, locus of control, and pedagogy manifested in participants’ EPT experiences? (2) What are participants’ views on the future of Kazakhstan’s private tutoring market? Data were collected through narrative writing and semi-structured interviews with eight students enrolled at a highly selective English-medium instruction (EMI) university. In terms of location, findings revealed that most participants favored small-group EPT because it was more affordable and they obtained balanced personalized attention with peer interaction. Regarding formality, participants reported significant parental influence in the decision to pursue EPT, as parents regarded English proficiency as essential for academic advancement and preferred private tutors over schoolteachers for their focus on high-stakes exam preparation. In the locus of control dimension, students were driven by short-term goals, such as achieving high IELTS scores, alongside long-term ambitions like pursuing international careers. The pedagogical dimension highlighted the value of individualized attention, which helped students strengthen academic writing, grammar, and speaking skills. Participants also recognized inequalities in access to quality EPT, especially between graduates of elite schools and those from mainstream schools. These disparities highlight the need to regulate the private tutoring sector to address tutor qualifications, pricing, and student safety in in-person and online contexts. The study concludes with recommendations for policy reforms, enhanced support within mainstream education, and further research on underrepresented groups, including rural students, parents, and tutors.
ЖОҒАРЫ БІЛІМГЕ ЖОЛ САТЫП АЛУҒА БОЛА МА? АҒЫЛШЫН ТІЛІНДЕГІ ЖЕКЕ РЕПЕТИТОРЛЫҚ КУРСТАРЫ ЖӘНЕ ОЛАРДЫҢ ҚАЗАҚСТАНДАҒЫ ТАҢДАУЛЫ АҒЫЛШЫН ТІЛІНДЕ ОҚЫТАТЫН УНИВЕРСИТЕТКЕ ТҮСУГЕ ЫҚПАЛЫ
ПЛАТНЫЙ ПУТЬ В ВЫСШЕЕ ОБРАЗОВАНИЕ? ЧАСТНОЕ РЕПЕТИТОРСТВО ПО АНГЛИЙСКОМУ ЯЗЫКУ И ЕГО ВЛИЯНИЕ НА ПОСТУПЛЕНИЕ В ПРЕСТИЖНЫЙ ВУЗ С АНГЛОЯЗЫЧНЫМ ОБУЧЕНИЕМ В КАЗАХСТАНЕ
Keywords: Private tutoring; English private tutoring; higher education; inequality; Central Asia; Type of access: Open